Pengaruh Model Pembelajaran Somatic Auditory Visualization Intelectually (SAVI) terhadap Keterampilan Sosial dan Hasil Belajar Kognitif Siswa Kelas X - Nining Erniati; Ida Royani; Ali Imran (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
This study aims to determine the effect of the Somatic Auditory Visualization Intellectually (SAVI) learning model on social skills and cognitive learning outcomes of students of class X MA NW Sanggeng in the 2016/2017 academic year. The type of research used is quasi-experimental (quasi-experimental). The research design used was pretest-posttest non-equivalent control group design. The population in this study were all students of class X MA NW Sanggeng in the 2016/2017 academic year as many as 33 people consisting of 2 classes, namely class X-A consisting of 16 students and class X-B consisting of 17 students. The sample of this study was taken with a saturated sample technique. Class X-A as the experimental class and class X-B as the control class. The instruments used in this study were lesson plans implementation sheets, student social skills observation sheets and student learning outcomes tests (objective or multiple choice tests). The data analysis technique used to analyze the data from this study was polled variance tests. The results of data analysis showed that there were differences in the improvement of cognitive learning outcomes between students who used the somatic auditory visualization intellectually (SAVI) learning model and students who did not use the somatic auditory visualization intellectual (SAVI) learning model. Social skills in the experimental class with an average value of 75% (active) and in the control class with an average value of 66.22% (active). The results of the t-test are known that the value of ????count is 5.237 which is consulted with at the 5% significance level of 1.696 so that ????count > ttable H0 is rejected (Ha is accepted). This means that there is an effect of using the somatic auditory visualization intellectually (SAVI) learning model on social skills and cognitive learning outcomes of class X MA NW Sanggeng students.